Effect of fermentation conditions on the production of hyaluronic acid by Streptococcus zooepidemicus ATCC 39920 - Pan, Nicole Caldas; Vignoli, Josiane Alessandra; Baldo, Cristiani; Pereira, Hanny Cristina Braga; Silva, Rui Sérgio dos Santos Ferreira; Celligoi, Maria Antonia Pedrine Colabone (Acta Scientiarum. Biological Sciences, 2015)
The production of hyaluronic acid by Streptococcus zooepidemicus ATCC 39920 with varying rates of pH (6.0, 7.0, 8.0), temperature (34; 37; 40°C), agitation (100, 150, 200 rpm), glucose (10, 20, 30 g L-1) and yeast extract concentration (10, 20, 30 g L-1) was evaluated by statistical approaches. The best conditions for the production of hyaluronic acid was pH 8.0, 37°C and 100 rpm in a medium containing 30 g L-1 glucose and yeast extract, for a production of 0.787 g L-1. Temperature, pH and yeast extract were significant variables (p < 0.05). Yeast extract and pH had a positive effect on the production of the polymer. Lactate, formate and acetate synthesis were also analyzed. Current assay showed the feasibility of statistical tools to optimize the physical and nutritional parameters for the production of hyaluronic acid and the improvement of the fermentation process.